Effects of dienogest treatment on endometrioma-related clinical symptoms and endometrioma size: retrospective cohort study - Ufuk Atlihan; Onur Yavuz; Can Ata; Huseyin Aytug Avsar; Selcuk Erkilinc (Frontiers in Medicine)
BackgroundTo evaluate the efficacy and long-term safety of treatment with dienogest in patients with endometrioma.MethodsPatients with endometrioma-related chronic pelvic pain were included in this retrospective study from March 2018 to March 2023. Enrolled patients received 2 mg of dienogest once daily. Data from 180 patients were analyzed. Group 2 (n = 104, 57.8%), comprising patients undergoing long-term therapy (>12 months), was compared with group 1 (n = 76, 42.2%), consisting of patients undergoing short-term therapy (<2 months), regarding their response to changes in endometrioma size and visual analog scale (VAS) scores. Statistical analysis was performed using the SPSS version 26.0 software. Non-normally distributed parameters were analyzed using the Mann–Whitney U test. In the evaluation of the data, apart from identifying statistical methods, the t-test was used in comparison of paired groups, and the matched t-test was used in the determination of changes before and after treatment. The Chi-square test and Fisher’s precision test were used in the analysis of categorical data. Categorical variables are presents as percentages, and quantitative variables are summarized as mean (95% confidence intervals) and median (minimum-maximum). p-values of <0.05 were considered statistically significant.ResultsFindings at T0 (baseline) and T1 (sixth month) visits, in which the entire study cohort could be included, were compared. Then, patients who continued treatment at visits every 6 months after T1 (>12 months) were compared one by one with the findings at T0. The reduced libido was 4.3 times higher in the long-term group, but the weight gain was higher in the short-term group. Analysis within all patients and individual groups (short term vs. long term) showed a significant decrease in endometrioma size and VAS scores between T0 and T1 visit findings. Similarly, the findings of T2 and each subsequent visit of the patients in the long-term group were compared with the initial findings and a significant reduction in endometrioma size and VAS scores was observed.ConclusionAlthough the effectiveness of dienogest treatment for endometrioma seems to begin in the sixth month, its effectiveness maximizes in patients whose treatment duration is over 1 year.